1996
DOI: 10.1097/00005537-199608000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Management of Airway Obstruction in Cicatricial Pemphigoid

Abstract: Cicatricial pemphigoid is a chronic vesiculobullous disease of the mucosal epithelium that primarily involves the oral cavity and the eyes. The clinical and histologic features are identical to those of bullous pemphigoid, and these features often can be nonspecific for other disease processes. It is not unusual for a period of 1 year or more to elapse before a diagnosis is made. The diagnosis of cicatricial pemphigoid requires characteristic lesions and histopathologic evidence of immunoglobulin deposition al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The articles identified from our search included 63 case reports7–58 and 10 case series,24, 59–66 representing 141 patients with laryngeal involvement of MMP. No clinical trials or comparative trials of laryngeal MMP were found.…”
Section: Resultsmentioning
confidence: 99%
“…The articles identified from our search included 63 case reports7–58 and 10 case series,24, 59–66 representing 141 patients with laryngeal involvement of MMP. No clinical trials or comparative trials of laryngeal MMP were found.…”
Section: Resultsmentioning
confidence: 99%
“…Also known as cicatricial pemphigoid, it is a vesiculobullous condition which primarily affects the oral cavity and eyes. Although rare, there are reported cases in the literature of MMP, causing epiglottic ulceration and oedema [71] or even as a large laryngeal mass encasing the glottis [72]. In both cases, an emergency tracheostomy was performed.…”
Section: Airway Managementmentioning
confidence: 99%
“…In both cases, an emergency tracheostomy was performed. There is some evidence of use of topical mitomycin in preventing laryngotracheal stenosis in cicatricial pemphigoid [71,73].…”
Section: Airway Managementmentioning
confidence: 99%
“…It was rst de ned as a separate pathological condition by Thorst 5 in 1911 and was termed benign mucous membrane pemphigoid in 1953 by Lever. 3 In 1980, Fisher 6 was the rst to describe laryngeal involvement in pemphigoid, and Drenger 7 was the rst to report airway obstruction in the disease in 1986.…”
Section: In 1988mentioning
confidence: 99%
“…Supraglottic scarring is treated effectively with the carbon dioxide laser. Whilst excision in the acute period is not recommended, 5 repeated division of laryngeal scar tissue may be necessary to stabilize the airway. Use of adjuvant mitomycin seems to reduce the severity of stenosis and lengthen the symptom-free interval.…”
Section: Treatmentmentioning
confidence: 99%